Čupori Moslavački: primjer plemićkog roda na području između rijeka Drave i Save - Nikolić Jakus, Zrinka (2011)
On the example of medieval kindred of Čupor from the area between the Sava and Drava rivers, several issues such as family structure, property acquisitions, public functions, relations with the ruler, clientage, and relations with the Church institutions are addressed. The general idea is to consider the mobility - social and spatial - of a typical clan of middling nobility within the Kingdom of Hungary. Special attention is given to the connection of the Čupor with the territory of present Slovakia as well as to a notorious story concerning one of family's members which offers some information about the use of word Tot as a term for Slav in the area south of Drava river.